Entrepreneurship from the Perspective of Tafsir Al-Misbah - Hanna Salsabila; Muhamad Yoga Firdaus; Ali Masrur (Gunung Djati Conference Series, 2021)
This study aims to discuss entrepreneurship with the Tafsir Al-Misbah perspective. This research method is qualitative through literature study with an interpretive approach. The results and discussion of this research include the notion of entrepreneurship, analysis of the Tafsir Al-Misbah, and entrepreneurship in the perspective of Tafsir Al-Misbah. This research concludes that the Al-Qur'an gives a message to always work hard, innovate, and take advantage of facilities for productivity. This study recommends that an in-depth study be carried out on other aspects of entrepreneurship to create new, more solutions